Security, Order and Community Obedience as Preconditions for Tourism Destination Competitiveness - Chairuddin, M. Awal; Syam, Husain; Akib, Haedar (Universitas Negeri Makassar, 2023)
be considered by the local government and stakeholders in each region. Security and order are